Microbial Assessment of Locally Compounded Herbals Tea Vended in Selected Markets Within Kaduna Metropolis - H. B. Sharif; S. Shitu; B. Abdullahi (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2023)
The study aims to evaluate microbial assessment of locally compounded herbal teas sold within Kaduna metropolis. A total of twenty samples of herbal teas were collected from various sellers situated at Bakin dogo and Kawo markets. The bacterial and fungal counts were conducted following the standard microbiological. Identification of the bacteria and fungi present in the samples were also performed using biochemical test and fungal stain. The bacterial count was found at a ranged from 9.0x104±6.3 cfu/g to 2.6x104±4.2 cfu/g. Aerobic spore-forming bacteria were recovered from the herbal teas. The fungal count ranged from 7.9x103±9.8 cfu/g to 6.9x104±3.5 cfu/g. The most common fungi and bacteria found in the herbal teas were Aspergillus spp. and Bacillus subtilis which were present in all herbal teas. The study unveiled that locally compounded herbal teas sold within Kaduna metropolis were contaminated with both bacteria and fungi at various levels indicating a potential risk for the regular consumer arising public health issues. Therefore, proper quality control should be constituted for herbal tea safety.